2018
DOI: 10.1002/aelm.201700631
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Trap States in Printed Indium Zinc Oxide Transistors by Doping with Benzyl Viologen

Abstract: the slow formation of self-assembled monolayers. [13] The contact resistances before and after doping are compared by the transmission-line method. In addition to typical current-voltage characteristics, the devices are characterized through capacitance and admittance measurements as a function of frequency and applied bias, to gain insights into charge transport affected by trap sites. Analyses of the cutoff frequency and the parallel conductance reveal the effective mobility and the density of trap states, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In particular, high mobility ink-jet printed IGZO TFTs with bottom-gate architecture and using a solution processed Sr-doped Al 2 O 3 (SAO) gate dielectric were fabricated by Choi et al [140], and exhibited on/off ratio and saturation field-effect mobility as high as 2.5 × 10 6 and 30.7 cm 2 /Vs, respectively. Behera et al [141] demonstrated high performance printed a-IZO FETs with field-effect mobility exceeding 27.5 cm 2 /Vs, well comparable to device mobility by inkjet printed a-IZO TFTs reported in previous works [142,143].…”
Section: Zno-based Formulations For Inkjet Printing and Related Devicessupporting
confidence: 54%
“…In particular, high mobility ink-jet printed IGZO TFTs with bottom-gate architecture and using a solution processed Sr-doped Al 2 O 3 (SAO) gate dielectric were fabricated by Choi et al [140], and exhibited on/off ratio and saturation field-effect mobility as high as 2.5 × 10 6 and 30.7 cm 2 /Vs, respectively. Behera et al [141] demonstrated high performance printed a-IZO FETs with field-effect mobility exceeding 27.5 cm 2 /Vs, well comparable to device mobility by inkjet printed a-IZO TFTs reported in previous works [142,143].…”
Section: Zno-based Formulations For Inkjet Printing and Related Devicessupporting
confidence: 54%
“…31,35−38 Because of poor charge transport in organic materials, the phototransistor structure is designed with separate channels 38 for charge photogeneration and transport, as shown in Figure 2g. In our bilayer phototransistors, the transport layer consists of indium zinc oxide (IZO), 39 on top of which is the infrared-responsive BHJ. Under illumination, the photogenerated holes are trapped in the polymer, while electrons are transferred to the IZO.…”
Section: Infrared-responsive Organic Semiconductors and Device Structmentioning
confidence: 99%
“…Furthermore, and in contrast to current capitalintensive vapor deposition growth, solution-processed a-MO films promise to reduce manufacturing costs (10)(11)(12)(13)(14) as well as enable flexible optoelectronics on inexpensive plastic substrates (15)(16)(17)(18)(19)(20)(21). This possibility reflects the substantial lowering of MO film-processing temperatures from >450-600°C to recently as low as 150-300°C (11,(22)(23)(24)(25)(26)(27)(28)(29). However, this dramatic temperature reduction has not been accompanied by a corresponding reduction in film-processing time, which remains far greater (presently 1-2 h minimum) than acceptable for efficient, continuous additive manufacture, as in typical FAB lines.…”
mentioning
confidence: 99%